Hypocomplementemic urticarial vasculitis syndrome: A disease with many faces - Ankit Agrawal; Sangeetha Pabolu; Shirisha Ale; Yesenia Galan (Indian Journal of Rheumatology)
Hypocomplementemic urticarial vasculitis syndrome (HUVS) is a rare autoimmune disease process where the exact pathogenesis is not known. It is an independent immunological condition affecting multiple organ systems. Major manifestations include chronic urticarial vasculitis (UV) with complement deficiency and demonstration of serum C1q antibodies. We describe a case of a 60-year-old male who presented with a generalized rash and was eventually diagnosed with HUVS. Usually, HUVS and systemic lupus erythematosus (SLE) have overlapping features, and our case was unique as our patient did not have any SLE manifestations. This article emphasizes the importance of comprehensive review of systemic manifestations accompanying UV. Although rare, it raises the awareness among the physicians about its clinical presentation and diagnostic approach and also predicts the prognosis of the same.